Slope Belts of Paleouplifts Control the Pore Structure of Organic Matter of Marine Shale: A Comparative Study of Lower Cambrian Rocks in the Sichuan Basin. (29th June 2021) - Wang, Pengfei; Zhang, Chen; Liu, Aorao; Zhang, Pengfei; Qiu, Yibo; Li, Xin; Yu, Shanshan; Yao, Shuqing; Liu, Sanyi; Jiang, Zhenxue
Abstract : Extensive exploration of the marine shale of the Niutitang Formation in south China has been conducted. However, exploration and development results have varied considerably in different areas. For example, the Niutitang shale in Jingyan City (Southwestern Sichuan Basin) produces a large amount of gas with a long period of stable production. In contrast, most development wells in the Niutitang shale in Chongqing City do not produce gas. Scanning electron microscopy images showed that the organic matter (OM) pore development in the Niutitang shale in Jingyan is abundant, large in size, and are well connected. In contrast, OM pores in the Niutitang shale in Chongqing are rarely observed. OM pore development of the Jingyan and Chongqing shales is mainly controlled by thermal maturity as shown by equivalent vitrine reflectance determinations. The moderate thermal maturity has resulted in the development of a large number of OM pores in the Niutitang shale in Jingyan, whereas the high thermal maturity of the Niutitang shale in Chongqing has led to the destruction of most of the OM pores. Due to the existence of ancient uplift, the shale was buried shallowly in the process of hydrocarbon generation evolution, and the shale avoided excessive thermal evolution and retained appropriate thermal maturity. In the Jingyan area, due to its location near the central uplift in the Sichuan Basin, the Niutitang shale deposited nearby avoided excessive evolution, and a large number of OM pores were retained in the reservoir.